Catalyst for producing hydrogen by electrolyzing water as well as preparation method and application of catalyst
By using Pt nanoparticles and WO3 nanorods in the electrolytic hydrogen evolution reaction catalyst, the problems of high platinum load and low utilization in the existing catalysts were solved, and the effect of significantly improving the catalytic efficiency under a lower platinum load was achieved.
Patent Information
- Application Number
- CN202510179217.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-02-18
AI Technical Summary
The existing electrolytic hydrogen evolution reaction catalyst has high loading, low utilization rate and low catalytic efficiency in the proton exchange membrane electrolysis tank.
A catalyst is provided that includes an active metal element Pt and a support WO3 nanorod. Pt is dispersed on the WO3 nanorod in the form of nanoparticles. The content of Pt is 1-10 wt%, the average diameter of the Pt nanoparticles is 1-5 nm, and the oxygen vacancy content of the catalyst is 12-20%. The catalyst is prepared by a specific preparation method, including mixing sodium tungstate dihydrate with sulfuric acid, adding a guide agent and drying, followed by mixing with a platinum source and undergoing drying and reducing treatment, and finally obtaining the catalyst.
By reducing the load of platinum in the cathode catalytic layer of the membrane electrode, the activity of the proton exchange membrane electrolytic cathode reaction is significantly improved, the comprehensive efficiency of the proton exchange membrane water electrolytic cell is improved, and the efficiency of the electrolytic device is improved.
Smart Images

Figure CN119753727A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a catalyst for producing hydrogen by electrolyzing water, and a preparation method and application thereof. Background Art
[0002] Hydrogen, with its cleanness, abundance and high energy density, is emerging as a promising energy carrier. However, hydrogen production through steam reforming using fossil fuels (i.e., coal and natural gas) is a significant source of large amounts of CO2 emissions. In contrast, electrolyzers use zero-emission wind / solar resources to electrolyze water into H2, providing an eco-friendly alternative. Hydrogen production through water electrolysis is considered to be a next-generation energy technology with great potential.
[0003] At present, common water electrolysis hydrogen production technologies include alkaline water electrolysis (AWE), proton exchange membrane water electrolysis (PEMWE) and high-temperature solid oxide water electrolysis (SOEC). Compared with alkaline water electrolysis and SOEC water electrolysis, PEM water electrolyzer has the advantages of higher tolerance to pressure difference, current fluctuation, system shutdown and cold start, and can maintain standby mode at the lowest power, which is well matched with wind power and photovoltaic with greater volatility and randomness. Because PEM electrolyzer is in a strong acidic environment and needs to withstand very high voltage (usually greater than 2V), the selection range of PEMWE component materials becomes narrow. Only some precious metal catalytic materials (Pt, Ir, Ru) and Ti collectors can meet the use requirements, which greatly increases the cost of water electrolysis devices.
[0004] Therefore, in order to address the key issue of high precious metal loading in PEMWE membrane electrodes, it is necessary to propose a strategy to reduce the platinum loading in the cathode catalyst layer of the membrane electrode and improve the efficiency of the water electrolysis device.
[0005] CN11788142A discloses a catalytic material, characterized in that it includes: a carrier; precious metal nanoparticles anchored on the surface of the carrier; an amorphous oxide layer coated on the surface of the precious metal nanoparticles; the composition of the amorphous oxide layer is MOx, wherein M is one of Mo, W, and V; the precious metal nanoparticles are one of Pt, Pd, Ru, Rh, or Ir nanoparticles, and the particle size of the nanoparticles is not greater than 4 nm. Although this scheme uses a similar method to try different metal oxide carriers and screens out amorphous Mo oxide-coated precious metal Pt particle catalytic materials with higher catalytic activity, this scheme does not verify that it can be used in PEMWE at ultra-low loading.
[0006] CN111298790A discloses a hydrogen evolution reaction catalyst, characterized in that the hydrogen evolution reaction catalyst is mainly composed of a non-metallic catalyst WO3, and WO3 is a WO3 nanosheet structure grown in situ on a flexible self-supporting substrate, and also includes Pt loaded on the surface of WO3 oxygen defects formed on the WO3 nanosheet in the form of atomic clusters. This scheme uses carbon fiber cloth as a substrate to first synthesize a carrier and then impregnate and load platinum. The hydrothermal amplification production using carbon cloth as a substrate has limitations. Although the platinum content in the synthesized catalyst of this scheme is low, the electrochemical hydrogen evolution activity is poor and the mass activity is low. When this scheme is applied, the platinum loading is only reduced to 1 / 3 of the commercial platinum loading; its application effect in PEMWE is also unpredictable.
[0007] CN111111658A discloses a single-atom Pt-loaded tungsten oxide single-layer nanosheet catalyst with ultra-high catalytic activity, characterized in that the microscopic morphology of the catalyst is: single-atom Pt is uniformly dispersed on the tungsten oxide single-layer nanosheet to form a single-layer nanosheet with a thickness of 0.7-1.3nm. The tungsten oxide in this scheme is a cubic phase, and the synthesis method is complex, time-consuming, multi-process, and energy-intensive; in this scheme, platinum is dispersed on the tungsten oxide nanosheet in the form of a single atom, and the platinum content in the catalyst is extremely low. Its catalytic activity has not been verified at high current density, and its stability is poor, and its application effect in PEMWE cannot be expected. Summary of the invention
[0008] The purpose of the present invention is to solve the problems of high platinum loading, low utilization rate and low catalytic efficiency of the prior art water electrolysis hydrogen evolution reaction catalyst after being applied to a proton exchange membrane water electrolysis tank.
[0009] In order to achieve the above-mentioned object, the first aspect of the present invention provides a catalyst for electrolyzing water to produce hydrogen, wherein the catalyst contains an active metal element Pt and a carrier WO3 nanorod; the active metal element Pt is dispersed on the carrier WO3 nanorod in the form of nanoparticles; based on the total mass of the catalyst, the content of the Pt is 1-10wt%;
[0010] The average diameter of the Pt nanoparticles in the catalyst is 1-5 nm, and the oxygen vacancy content of the catalyst is 12-20%.
[0011] The second aspect of the present invention provides a method for preparing the catalyst described in the first aspect, the method comprising:
[0012] (1) mixing a sodium tungstate dihydrate aqueous solution with sulfuric acid to obtain a first solution; the concentration of the sodium tungstate dihydrate solution is 30-40 mg / mL; and the amount of sulfuric acid is such that the pH value of the first solution is 1-2;
[0013] (2) reacting the directing agent with the first solution, and performing a first drying on the obtained product to obtain WO3 nanorods; the mass ratio of the sodium tungstate dihydrate to the directing agent is 1:3-4; the reaction conditions include: a temperature of 160-190° C. and a reaction time of 10-24 h;
[0014] (3) in the presence of water, mixing the platinum source and the WO3 nanorods for a third time, and drying the obtained product for a second time to obtain a catalyst precursor; the platinum source and the WO3 nanorods are used in a mass ratio of 1:10-40 in terms of platinum element and WO3 nanorods, respectively;
[0015] (4) The catalyst precursor is subjected to a reduction treatment to obtain the catalyst.
[0016] The third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0017] The fourth aspect of the present invention provides use of the catalyst described in the first aspect and / or the third aspect in a hydrogen production reaction by electrolysis of water.
[0018] The abundant oxygen vacancies in the WO3 nanorods in the catalyst provided by the present invention provide abundant anchoring sites for Pt, and at the same time, Pt is highly dispersed on the surface of the WO3 nanorods, has a large specific surface area, and can give full play to the efficiency of the Pt element.
[0019] The catalyst provided by the present invention can provide continuous proton transfer and electron transfer channels, greatly reducing the platinum loading in the membrane electrode cathode catalyst layer. At a lower platinum loading, the activity of the cathode reaction of the proton exchange membrane water electrolysis is significantly improved, the overall efficiency of the proton exchange membrane water electrolyzer is improved, and the efficiency of the water electrolysis device is improved.
[0020] Furthermore, the method for preparing the catalyst provided by the present invention is simple to operate, environmentally friendly, and easy to control and scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is an electron microscope image of WO3 nanorods and catalyst obtained in Example 1 provided by the present invention;
[0022] Figure 2 is an electron microscope image of the catalyst obtained in Example 2 provided by the present invention;
[0023] Figure 3 is an electron microscope image of WO3 nanorods and catalyst obtained in Example 3 provided by the present invention;
[0024] Figure 4 is an electron microscope image of WO3 nanorods obtained in Example 4 provided by the present invention;
[0025] Figure 5 is an electron microscope image of the catalyst obtained in Example 6 provided by the present invention;
[0026] Figure 6 This is an electron microscope image of the WO3 carrier obtained in Comparative Example 2 provided by the present invention;
[0027] Figure 7 is an electron microscope image of the WO3 carrier obtained in Comparative Example 5 provided by the present invention;
[0028] Figure 8 HRTEM images of WO3 nanorods and catalysts obtained in Example 1 provided by the present invention;
[0029] Fig. 9 is an EDS graph of the catalyst obtained in Example 1 provided by the present invention;
[0030] Fig.10 is an XPS graph of the catalyst obtained in Example 1 provided by the present invention;
[0031] Fig.11 is an XPS graph of the catalyst obtained in Comparative Example 4 provided by the present invention;
[0032] Fig.12 is an XRD comparison diagram of the catalysts obtained in Example 1, Example 2 and Comparative Example 3 provided by the present invention;
[0033] Fig.13 It is a comparison diagram of polarization curves of catalysts obtained in Example 1 and Comparative Example 4 provided by way of example in the present invention. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] As mentioned above, the first aspect of the present invention provides a catalyst for electrolyzing water to produce hydrogen, the catalyst comprising an active metal element Pt and a carrier WO3 nanorod; the active metal element Pt is dispersed on the carrier WO3 nanorod in the form of nanoparticles; based on the total mass of the catalyst, the content of Pt is 1-10wt%;
[0036] The average diameter of the Pt nanoparticles in the catalyst is 1-5 nm, and the oxygen vacancy content of the catalyst is 12-20%.
[0037] Preferably, based on the total mass of the catalyst, the content of Pt is 3-4 wt%.
[0038] More preferably, the average diameter of the Pt nanoparticles in the catalyst is 1-2 nm, and the oxygen vacancy content of the catalyst is 16.5-17.2%.
[0039] Further preferably, the WO3 nanorods have an average length of 100-200 nm and an average diameter of 10-20 nm.
[0040] As mentioned above, the second aspect of the present invention provides a method for preparing the catalyst described in the first aspect, the method comprising:
[0041] (1) mixing a sodium tungstate dihydrate aqueous solution with sulfuric acid to obtain a first solution; the concentration of the sodium tungstate dihydrate solution is 30-40 mg / mL; and the amount of sulfuric acid is such that the pH value of the first solution is 1-2;
[0042] (2) reacting the directing agent with the first solution, and performing a first drying on the obtained product to obtain WO3 nanorods; the mass ratio of the sodium tungstate dihydrate to the directing agent is 1:3-4; the reaction conditions include: a temperature of 160-190° C. and a reaction time of 10-24 h;
[0043] (3) in the presence of water, mixing the platinum source and the WO3 nanorods for a third time, and drying the obtained product for a second time to obtain a catalyst precursor; the platinum source and the WO3 nanorods are used in a mass ratio of 1:10-40 in terms of platinum element and WO3 nanorods, respectively;
[0044] (4) The catalyst precursor is subjected to a reduction treatment to obtain the catalyst.
[0045] Preferably, in step (1), the concentration of sulfuric acid is 3-5 mol / L.
[0046] Preferably, the first mixing condition includes: a temperature of 25-30°C.
[0047] More preferably, the first mixing is performed under stirring conditions, the stirring speed is 200-500 rpm, and the time is 0.25-0.5 h.
[0048] Preferably, in step (2), the directing agent is a combination of sulfate and dihydrated oxalic acid in a molar ratio of 3-4:1; the sulfate is selected from at least one of ammonium sulfate and sodium sulfate; more preferably ammonium sulfate. The inventors have found that under this preferred embodiment, the catalyst obtained by the present invention has better catalytic activity and has a higher current density after being applied to a water electrolysis device.
[0049] Preferably, in step (2), the reaction is carried out in a reactor, and the reaction conditions include: temperature of 175-185° C. and time of 10-12 h.
[0050] Preferably, the reaction is carried out under stirring conditions, and the stirring speed is 200-500 rpm.
[0051] More preferably, in step (2), the method further comprises: before the reaction, first subjecting the directing agent to a second mixing with the first solution, wherein the conditions of the second mixing include: a stirring speed of 200-500 rpm, a time of 20-30 min, and a temperature of 20-30°C.
[0052] It should be noted that in step (2), the present invention has no special requirements for the reaction kettle, as long as it can meet the high temperature and high pressure required for the reaction. The present invention will not be described in detail here, and those skilled in the art should not interpret this as a limitation of the present invention.
[0053] Preferably, in step (3), the platinum source is selected from at least one of H2PtCl6·6H2O, potassium chloroplatinate and cisplatin.
[0054] More preferably, the platinum source is a platinum source aqueous solution with a concentration of 10-30 mg / mL.
[0055] Preferably, in step (3), the amount of water used is 20-40 mL relative to 100 mg of WO3 nanorods.
[0056] Preferably, the third mixing is performed under stirring conditions, and the third mixing conditions include: a temperature of 50-90°C, more preferably 60-90°C; a time of 10-14h, more preferably 11-12h. The inventors found that under this preferred embodiment, the catalyst obtained by the present invention has more active sites exposed, the dispersion of metal platinum is more uniform, and the electrochemical performance is better after being applied to the water electrolysis device.
[0057] Preferably, in step (4), the reduction treatment is carried out in the presence of a reducing atmosphere, and the conditions of the reduction treatment include: a heating rate of 2-5°C / min, a temperature of 350-450°C, and a time of 3-5h.
[0058] More preferably, the reducing atmosphere is a combination of hydrogen and argon, and the content of hydrogen is 4-6% by volume.
[0059] As mentioned above, the third aspect of the present invention provides a catalyst prepared by the method described in the second aspect.
[0060] As mentioned above, the fourth aspect of the present invention provides the use of the catalyst described in the first aspect and / or the third aspect in the reaction of producing hydrogen by electrolysis of water.
[0061] Preferably, the catalyst is used in proton exchange membrane water electrolysis to produce hydrogen;
[0062] More preferably, the catalyst loading in the membrane electrode is no more than 0.05 mg / cm 2 .
[0063] The present invention will be described in detail below through examples. In the following examples, unless otherwise specified, the raw materials and equipment used are commercially available, and the raw materials are all analytically pure.
[0064] Example 1
[0065] This example is used to illustrate that the catalyst for producing hydrogen by electrolysis of water provided by the present invention is prepared by the following steps:
[0066] (1) 1.32 g of sodium tungstate dihydrate was dissolved in 40 mL of water to obtain a sodium tungstate dihydrate aqueous solution with a concentration of 33 mg / mL, and then mixed with 5 mol / L sulfuric acid (stirring speed was 300 rpm, time was 1 h, temperature was 25° C.) to obtain a first solution; the amount of sulfuric acid used was such that the pH value of the first solution was 1;
[0067] (2) In a reaction vessel, the directing agent and the first solution are mixed for a second time (stirring speed is 400 rpm, time is 30 min, temperature is 25° C.), and then reacted, and the obtained product is dried for a first time (dried at 50° C. for 5 h) to obtain WO3 nanorods;
[0068] The mass ratio of the sodium tungstate dihydrate to the directing agent is 1:3.8;
[0069] The reaction conditions are: temperature 180°C, time 10h;
[0070] The directing agent is a combination of ammonium sulfate and oxalic acid dihydrate in a molar ratio of 4:1;
[0071] (3) dispersing 100 mg of the WO3 nanorods in 30 mL of water, and then mixing with a 30 mg / mL chloroplatinic acid aqueous solution for a third time, and performing rotary evaporation and second drying (50° C. for 5 h) on the obtained product in sequence to obtain a catalyst precursor;
[0072] The mass ratio of the platinum source and the WO3 nanorods is 1:33.3, calculated as platinum element and WO3 nanorods, respectively;
[0073] The third mixing conditions are: temperature of 80°C, time of 12h, stirring speed of 500rpm;
[0074] (4) subjecting the catalyst precursor to a reduction treatment to obtain the catalyst S1;
[0075] The reduction treatment conditions are as follows: the reducing atmosphere is a combination of 5 volume % hydrogen and 95 volume % argon, the heating rate is 5° C. / min, the temperature is 400° C., and the time is 4 hours.
[0076] Example 2
[0077] (1) 1.32 g of sodium tungstate dihydrate was dissolved in 33 mL of water to obtain a sodium tungstate dihydrate aqueous solution with a concentration of 40 mg / mL, and then mixed with 5 mol / L sulfuric acid (stirring speed was 500 rpm, time was 0.5 h, temperature was 25° C.) to obtain a first solution; the amount of sulfuric acid used was such that the pH value of the first solution was 1.5;
[0078] (2) In a reaction vessel, the directing agent and the first solution are mixed for a second time (stirring speed is 400 rpm, time is 30 min, temperature is 25° C.), and then reacted, and the obtained product is dried for a first time (dried at 50° C. for 5 h) to obtain WO3 nanorods;
[0079] The mass ratio of the sodium tungstate dihydrate to the directing agent is 1:3.5;
[0080] The reaction conditions are: temperature 170°C, time 12h;
[0081] The directing agent is a combination of ammonium sulfate and oxalic acid dihydrate in a molar ratio of 3:1;
[0082] (3) dispersing 100 mg of the WO3 nanorods in 30 mL of water, and then mixing with a 20 mg / mL chloroplatinic acid aqueous solution for a third time, and performing rotary evaporation and second drying (50° C. for 5 h) on the obtained product in sequence to obtain a catalyst precursor;
[0083] The platinum source and the WO3 nanorods are used in a mass ratio of 1:11 in terms of platinum element and WO3 nanorods, respectively;
[0084] The third mixing conditions are: temperature of 60°C, time of 11h, stirring speed of 500rpm;
[0085] (4) subjecting the catalyst precursor to a reduction treatment to obtain the catalyst S2;
[0086] The reduction treatment conditions are as follows: the reducing atmosphere is a combination of 5 volume % hydrogen and 95 volume % argon, the heating rate is 2° C. / min, the temperature is 450° C., and the time is 5 h.
[0087] Example 3
[0088] This example is carried out using a process similar to that of Example 1, except that in this example, the directing agent is a combination of sodium sulfate and oxalic acid dihydrate in a mass ratio of 4:1.
[0089] The rest are the same as in Example 1.
[0090] Catalyst S3 was prepared.
[0091] Example 4
[0092] This example is carried out using a process similar to that of Example 1, except that in this example, in step (2), the reaction conditions are: time is 24 hours.
[0093] The rest are the same as in Example 1.
[0094] Catalyst S4 was prepared.
[0095] Example 5
[0096] This embodiment is carried out using a process similar to that of Embodiment 1, except that in this embodiment, in step (3), the temperature of the third mixing is 25°C.
[0097] The rest are the same as in Example 1.
[0098] Catalyst S5 was prepared.
[0099] Example 6
[0100] This embodiment adopts a process similar to that of Embodiment 1, except that the reduction treatment conditions in this embodiment are: the reducing atmosphere is N2.
[0101] The rest are the same as in Example 1.
[0102] Catalyst S6 was prepared.
[0103] Comparative Example 1
[0104] This comparative example is carried out using a process similar to that of Example 1, except that in this comparative example, tungstic acid of equal mass is used to replace the sodium tungstate dihydrate in Example 1.
[0105] The rest are the same as in Example 1.
[0106] Catalyst DS1 was prepared.
[0107] Comparative Example 2
[0108] This comparative example is carried out using a process similar to that of Example 1, except that in this comparative example, in step (1), the amount of sulfuric acid used is such that the pH value of the first solution is 0.3.
[0109] The rest are the same as in Example 1.
[0110] Catalyst DS2 was prepared.
[0111] Comparative Example 3
[0112] This comparative example is carried out using a process similar to that of Example 1, except that in this comparative example, the prepared catalyst does not contain platinum. The specific preparation steps are as follows:
[0113] (1) Same as Example 1;
[0114] (2) Same as Example 1;
[0115] (3) 100 mg of WO3 nanorods were subjected to reduction treatment (the reduction treatment conditions were the same as those in Example 1) to obtain the material DS3.
[0116] Comparative Example 4
[0117] Commercial Pt / C (Pt content of 40% by mass) was purchased from Zhengzhou Alpha Chemical Co., Ltd.
[0118] Comparative Example 5
[0119] This example is carried out using a process similar to that of Example 1, except that in this example, in step (2), the reaction conditions are: the temperature is 150°C.
[0120] The rest are the same as in Example 1.
[0121] Catalyst DS5 was prepared.
[0122] The composition and parameter characteristics of the catalysts prepared in the above examples are shown in Table 1; wherein the content of the Pt element is detected by an ICP-MS detector.
[0123] Table 1
[0124]
[0125] Table 1 (Continued)
[0126]
[0127]
[0128] Note: “ / ” in Table 1 means that the test results have not been tested or have no practical significance.
[0129] The present invention also exemplarily provides an electron microscope image of the catalyst prepared in the above example, Figure 1 The WO3 nanorods provided in Example 1 ( Figure 1 (a) and Figure 1 (b) is an electron microscope image of the catalyst under different shooting angles. Figure 1 (c) and Figure 1 The electron microscope image of (d) Figure 1 It can be seen that the prepared WO3 carrier is in the shape of a rod, and the metal element Pt is dispersed on the carrier WO3 nanorods in the form of nanoparticles.
[0130] Figure 2 The electron microscope image of the catalyst provided for Example 2, from Figure 2 It can be seen that the prepared WO3 carrier is in a rod shape, and the metal element Pt is dispersed on the carrier WO3 nanorods in the form of nanoparticles. Compared with the catalyst provided in Example 1, the size of the platinum element particles is larger.
[0131] Figure 3 The WO3 nanorods provided in Example 3 ( Figure 3 (a) and Figure 3 (b) is an electron microscope image taken at different viewing angles) and the catalyst ( Figure 3 (c) and Figure 3 (d) is an electron microscope image taken at different shooting angles. Figure 3 (a) and Figure 3 It can be seen from (b) that when the directing agent used is a combination of sodium sulfate and oxalic acid dihydrate in a mass ratio of 4:1, the size of the prepared WO3 nanorods increases significantly.
[0132] Figure 4 The electron microscope image of the WO3 nanorods provided in Example 4 is shown in FIG. Figure 4 It can be seen that in step (2), after the reaction time is set to 24 h, the size of the nanorods is uneven, and some nanorods with larger sizes, especially larger diameters, are formed.
[0133] Figure 5 The electron microscope image of the catalyst provided for Example 6, from Figure 6 It can be seen that when the reducing atmosphere is N2, the Pt nanoparticles loaded on the prepared catalyst can hardly be clearly seen, indicating that the loading amount of Pt nanoparticles is low.
[0134] Figure 6 The electron microscope image of the WO3 carrier provided for Comparative Example 2 is shown in FIG. Figure 6It can be seen that in step (1), when the pH value of the first solution is 0.3, the prepared sample has an irregular morphology.
[0135] Figure 7 The WO3 carrier provided in Comparative Example 5 is Figure 7 It can be clearly seen that the prepared samples have irregular morphology.
[0136] Figure 8 HRTEM images of WO3 nanorods and catalysts prepared in Example 1, wherein (a), (b), and (c) are HRTEM images of WO3 nanorods prepared in Example 1, from which lattice fringes with a spacing of 0.37 nm can be seen, belonging to the 110 crystal plane of WO3; wherein (d), (e), and (f) are HRTEM images of the catalyst prepared in Example 1, from which lattice fringes belonging to the 111 crystal plane of Pt can be observed, with a spacing of 0.23 nm.
[0137] The present invention also exemplarily provides an EDS image of the catalyst obtained in Example 1 ( Fig. 9 ),from Fig. 9 It can be clearly seen that the active metal element Pt is evenly dispersed on the carrier WO3 nanorods in the form of nanoparticles.
[0138] The present invention also exemplarily provides Example 1 ( Fig.10 ) and Comparative Example 4 ( Fig.11 ) of the XPS graph, from Fig.10 It can be clearly seen that the oxygen vacancy content of the catalyst is 16.96%. Fig.10 and Fig.11 It can be seen that the platinum in commercial catalysts is mainly Pt and Pt 2+ , while the Pt in the catalyst prepared in Example 1 is mainly Pt 2+ Form exists.
[0139] The present invention also exemplarily provides XRD patterns of Example 1 (S1), Example 2 (S2) and Comparative Example 3 (DS3) (eg Fig.12 shown), from Fig.12 It can be clearly seen that both Example 1 (S1) and Comparative Example 3 (DS3) correspond to the PDF#85-2460 standard card of WO3, but due to the low content of platinum, no obvious diffraction peak belonging to Pt is observed in Example 1.
[0140] Test Example 1
[0141] The electrocatalytic hydrogen evolution performance of the catalyst provided in the above examples was tested.
[0142] The above samples were tested using a three-electrode system, with a saturated calomel electrode (SCE) as the reference electrode, a carbon rod electrode as the counter electrode, and H2-saturated 0.5 M H2SO4 as the electrolyte. The test was performed using a Shanghai Chenhua CHI 760e electrochemical workstation.
[0143] The preparation method of the working electrode is as follows: weigh 5 mg of the prepared catalyst sample, disperse it in 1 mL of a mixed solvent of ultrapure water and isopropanol (volume ratio of 3:1), then add 20 μL of a 5 wt% Nafion membrane solution and 1 mg of carbon black as a conductive agent. Ultrasonic dispersion is performed for 30 min using an ultrasonic processor at room temperature to obtain a uniform catalyst dispersion, and 13.33 μL and 2.5 μL of the above catalyst dispersion are respectively applied to a platinum carbon electrode (d = 5 mm) to form a platinum loading of 10 μg / cm after the surface is completely dried. 2 and 1.875 μg / cm 2 The working electrode, reference electrode, and counter electrode were used to form a three-electrode system for linear sweep voltammetry (LSV) and chronoamperometric tests. The test results are shown in Table 2 and Table 3, respectively, depending on the different platinum loadings of the working electrode.
[0144] Table 2
[0145] <![CDATA[10mA·cm -2 Overpotential at]]> Example 1 9.8mV Example 2 12.6mV Example 3 13.2mV Example 4 20.1mV Example 5 21.3mV Example 6 24.6mV Comparative Example 1 / Comparative Example 2 42.6mV Comparative Example 3 / Comparative Example 4 25.2mV Comparative Example 5 /
[0146] Note: The “ / ” in Table 2 indicates the 10 μg / cm prepared using the catalyst 2 The working electrode with platinum loading is 10 mA cm -2 The overpotential at the current density is too high, which directly indicates that the catalyst has basically no electrochemical hydrogen evolution activity.
[0147] From the results in Table 2, it can be seen that the hydrogen evolution performance of the catalyst was tested under the three-electrode system at 10 mA cm -2 The overpotential of the catalyst provided by the present invention is used as an indicator to evaluate its electrochemical activity. The catalyst provided by the present invention exhibits higher hydrogen evolution activity than the comparative example, 10 mA·cm -2 The overpotentials are all within 25mV.
[0148] Table 3
[0149]
[0150]
[0151] Note: The “ / ” in Table 3 indicates 1.875 μg / cm prepared using catalyst 2 The working electrode with platinum loading is 10 mA cm -2 The overpotential at the current density is too high, which directly indicates that the catalyst has basically no electrochemical hydrogen evolution activity.
[0152] From the results in Table 3, it can be seen that the platinum loading on the working electrode is reduced to 1.875 μg / cm 2 When the electrochemical activity of the catalyst obtained by the present invention is 10 μg / cm 2 The catalyst obtained in Example 1 has the smallest difference before and after the platinum loading is reduced, 10 mA·cm -2 The overpotentials are all within 15 mV. It can be calculated that the mass activity of the catalyst obtained in Example 1 at an overpotential of 50 mV can reach 14.285 A mg -1 Pt.
[0153] Test Example 2
[0154] A customized PEMWE electrolytic cell was used to evaluate the performance of two-electrode water electrolysis.
[0155] The test method is:
[0156] Preparation method of membrane electrode: The catalyst prepared in the above-mentioned Example 1 (S1) and Comparative Example 4 (DS4) is prepared to have a platinum loading of 0.05 mg / cm 2 The catalyst slurry K was prepared with an iridium loading of 1.2 mg / cm 2 Commercial IrO2 catalyst slurry is used, and cathode catalyst catalyst slurry K and commercial IrO2 catalyst slurry are sprayed on both sides of the proton exchange membrane N212 respectively. The gas diffusion layer on the cathode side uses hydrophilic carbon paper, and the gas diffusion layer on the anode side uses commercial platinum-coated titanium felt to obtain the membrane electrode used for the test.
[0157] The flow battery consists of a corrosion-resistant titanium plate (anode bipolar plate) and a graphite plate (cathode bipolar plate), on which a single three-snake flow field (area 4.0 cm 2 ); the end plate is made of corrosion-resistant 316 stainless steel (SUS 316), the gas diffusion layer on the cathode side is made of hydrophilic carbon paper, and the gas diffusion layer on the anode side is made of commercial platinum-coated titanium felt. The prepared membrane electrode is placed between the anode and cathode bipolar plates, with the cathode catalyst layer facing the hydrophilic carbon paper and the anode catalyst layer facing the platinum-coated titanium felt.
[0158] The temperature of the electrolytic cell was maintained at 60°C, and deionized water was continuously pumped into the anode flow field by a peristaltic pump at a flow rate of 100 sccm. The polarization curve was obtained with the cooperation of an electrochemical workstation (Solartron) and a 20A current intensifier. Before the water electrolysis measurement, the prepared MEA was activated by cyclic voltammetry (1.2V~2.0V) until the battery reached the target temperature. The polarization curve of the battery was obtained at a scan rate of 10mV·s-1. The results are shown in Fig.13 .
[0159] from Fig.13 It can be clearly seen that 40% commercial platinum carbon (DS4) reaches 1A·cm at a voltage of 1.95V. -2 The catalyst (S1) provided by the present invention has a platinum loading of 0.05 mg / cm 2 When the voltage is 1.74V, it can reach 1A·cm -2 The current density reached 2A cm at a voltage of 1.94V. -2 The current density is much higher than that of 40% commercial platinum carbon at the same platinum loading. This shows that the catalyst provided by the present invention can still well demonstrate the performance of platinum-based catalysts at extremely low platinum loadings, and ensures the high activity of electrode materials under the premise of greatly reducing the precious metal platinum loading, showing good application prospects in PEMWE devices.
[0160] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst for producing hydrogen by electrolysis of water, characterized in that: The catalyst contains active metal element Pt and carrier WO3 nanorods; the active metal element Pt is dispersed on the carrier WO3 nanorods in the form of nanoparticles; based on the total mass of the catalyst, the content of Pt is 1-10wt%; The average diameter of the Pt nanoparticles in the catalyst is 1-5 nm, and the oxygen vacancy content of the catalyst is 12-20%.
2. The catalyst according to claim 1, characterized in that Based on the total mass of the catalyst, the content of Pt is 3-4wt%; and / or, the average diameter of the Pt nanoparticles in the catalyst is 1-2 nm, and the oxygen vacancy content of the catalyst is 16.5-17.2%; And / or, the WO3 nanorods have an average length of 100-200 nm and an average diameter of 10-20 nm.
3. A method for preparing the catalyst according to claim 1 or 2, characterized in that: The method includes: (1) mixing a sodium tungstate dihydrate aqueous solution with sulfuric acid to obtain a first solution; the concentration of the sodium tungstate dihydrate solution is 30-40 mg / mL; and the amount of sulfuric acid is such that the pH value of the first solution is 1-2; (2) reacting the directing agent with the first solution, and performing a first drying on the obtained product to obtain WO3 nanorods; the mass ratio of the sodium tungstate dihydrate to the directing agent is 1:3-4; the reaction conditions include: a temperature of 160-190° C. and a reaction time of 10-24 h; (3) in the presence of water, mixing the platinum source and the WO3 nanorods for a third time, and drying the obtained product for a second time to obtain a catalyst precursor; the mass ratio of the platinum source and the WO3 nanorods is 1:10-40 in terms of platinum element and WO3 nanorods respectively; (4) The catalyst precursor is subjected to a reduction treatment to obtain the catalyst.
4. The method according to claim 3, characterized in that In step (1), the concentration of sulfuric acid is 3-5 mol / L; And / or, the first mixing condition includes: a temperature of 25-30°C.
5. The method according to claim 3 or 4, characterized in that: In step (2), the directing agent is a combination of sulfate and oxalic acid dihydrate in a molar ratio of 3-4:1; The sulfate is selected from at least one of ammonium sulfate and sodium sulfate; preferably ammonium sulfate.
6. The method according to any one of claims 3 to 5, characterized in that: In step (2), the reaction is carried out in a reactor, and the reaction conditions include: temperature 170-185° C., and time 10-12 h.
7. The method according to any one of claims 3 to 6, characterized in that: In step (3), the platinum source is selected from at least one of H2PtCl6·6H2O, potassium chloroplatinate, and cisplatin; Preferably, the platinum source is a platinum source aqueous solution with a concentration of 10-30 mg / mL; And / or, the third mixing is performed under stirring conditions, and the conditions of the third mixing include: a temperature of 50-90° C., preferably 60-90° C.; and a time of 10-14 h, preferably 11-12 h.
8. The method according to any one of claims 3 to 7, characterized in that: In step (4), the reduction treatment is carried out in the presence of a reducing atmosphere, and the conditions of the reduction treatment include: a heating rate of 2-5°C / min, a temperature of 350-450°C, and a time of 3-5h; Preferably, the reducing atmosphere is a combination of hydrogen and argon, and the content of hydrogen is 4-6 volume %.
9. A catalyst prepared by the method according to any one of claims 3 to 8.
10. Use of the catalyst according to any one of claims 1, 2 and 9 in the reaction of producing hydrogen by electrolysis of water; Preferably, the catalyst is used in proton exchange membrane water electrolysis to produce hydrogen; More preferably, the catalyst loading in the membrane electrode is no more than 0.05 mg / cm 2 .
Citation Information
Patent Citations
Pt atomic cluster loaded WO3 nanosheet hydrogen evolution reaction catalyst and preparation method thereof
CN111298790A
Precious metal nanoparticle catalytic material wrapped by amorphous oxide as well as preparation method and application of precious metal nanoparticle catalytic material
CN117888142A
Supported CuPt bimetallic active site catalyst as well as preparation method and application thereof
CN118217969A
Cited By
Tungsten oxide supported palladium-silver catalyst with high specific surface area as well as preparation method and application of tungsten oxide supported palladium-silver catalyst
CN120497362A